Anxiety, Depression and Diabetes-Associated Distress in Subjects with Type 1 Diabetes Mellitus - Hussain, Sana; Afaq, Saima; Jawad, Muhammad; Saif, Laila; Fatima, Razia (ADVANCES IN BASIC MEDICAL SCIENCES, 2022)
Objective: To determine the frequency of anxiety, depression, and diabetes-associated distress in type 1 diabetes mellitus patients. Methodology: This cross-sectional study was conducted at the Sugar Hospital of the Abasyn Institute of Medical Sciences, Peshawar, Pakistan. This study was based on using standardized questionnaires i.e. the Patient Health Questionnaire (PHQ-9), Generalized Anxiety Disorder (GAD-7), and Problem Areas in Diabetes scale (PAID-5), respectively. Patients with T1DM were evaluated for anxiety, depression, and diabetes-related distress. Data have been analyzed to assess the prevalence and danger factors for depression, anxiety, and diabetes-related distress in this population. Results: Children and adults suffering from T1DM (n = 80) with mean age of 18±6 years; with 53% male and 47% female subjects. Out of the total 80 patients, 77% had poor glycemic control and 72.5% had depression. Severe depression and severe anxiety had been existing in 15% and 36% of patients respectively. Diabetes-associated distress was experienced by 59% of patients, and a significant association of anxiety was found with the patient’s glycemic control and education level. Conclusion: In this study mental issues are extremely common in T1DM patients, and prevelance is more with poor glycemic control. Keywords: T1DM, Anxiety, Depression, Diabetes-associated Distress.